Self-reported low back pain intensity and interferences among three-wheel drivers in Southwest of Ethiopia: A Community-Based Cross-sectional Study - Kebede, Ebissa Bayana; Terfa, Yonas Biratu; Tucho, Abdisa Eba; Germossa, Gugsa Nemera; Hailu, Fikadu Balcha; Abdisa, Birhanu; Mamo, Selam Ayele; Enbakom, Mestawet Getachew; Akuma, Adugna Olani (International Journal of Occupational Safety and Health, 2023)
Introduction: Low back pain is one of the most reported conditions among vehicle drivers. However, there is a paucity of information about low back pain experiences among three-wheel drivers in Ethiopia. This study aimed to determine the low back pain experience among three-wheel drivers in Ethiopia Jimma City, Southwest Ethiopia.Methods: A Community-based cross-sectional study was conducted from March 1-25, 2020 among 396 samples. Computer generated simple random sampling method was employed to get the required sample. An interviewer-administered questionnaire was used to collect the data. The data was checked for completeness, coded, cleaned and entered into Epi-data version 3.1 and exported to SPSS version 23 for analysis. Data was analyzed using mean and standard deviations for continuous and proportions for categorical variables. Binary and multivariable logistic regression was used to see an association between dependent and independent variables. P-value